Linguagem verbo: visual dos gêneros textuais no livro didático de alfabetização - Colaço, Erika Maria da Rocha (2016)
This study arose from the following questions: First, the verbal-visual texts displayed in the reading section in textbooks are suitable for children s literacy, from the viewpoint of the relationship between word and image? Second, the images brought in the reading section of textbooks are appropriate for children´s literacy or they function as mere accessories in the textbooks? In attempting to understand the study s subject - the textbook - we elaborated the following objective: to examine the meanings coming from the relationship between the verbal and the visual language in different genres in textbooks for children s literacy cycle, based on the PNLD 2013 s Textbook Guide. As the theoretical foundation for genres, we used rhetoric and sociological approaches. For language concepts like language, text, discourse and genre s support we used Text Linguistics. For the discussion on visual language, we sought the framework of Peirce's semiotics in the perspective developed by Santaella (2012). The contextualization of textbooks was supported on Rojo (2009), among others. In order to undertake a research of qualitative approach, for data collection we made a prior analysis of didactic materials, from which we selected the samples of genres in three textbooks collections (the corpus for the research). For the relationship between the interpretation of image and the verbal context, we used the semantic categories proposed by Santaella (2012), that is to say: a) dominance; b) redundancy; c) complementarity and d) discrepancy or contradiction. The obtained results reveal that the three collections meet the requirements of the genre diversity and of multi-semiotic aspects. It was found that the prevailing combination of verbal and visual language is one of complementarity, although the category of redundancy also has been identified. The categories of discrepancy or contradiction and of dominance appeared sporadically in the corpus. Thus, for fostering verbal and imagistic literacy, we argue that Portuguese language education must be based on texts, and emphasize other semiotic systems in addition to the verbal. It follows that, nowadays, there is an urgency for research continuity on the relationship between verbal language and visual language in different genres, and this may greatly help the teaching of the mother tongue in children s literacy cycle and in the subsequent levels of literacy.